Analysis on the status and influencing factors of the clinical communication competency of male psychiatric nurses in Guangdong Province (广东省精神科男护士临床沟通能力现状及影响因素分析) - ZOU Caimei (邹彩媚); ZENG Junfang (曾君芳); HUANG Jieying (黄洁英); ZHUANG Jingyi (庄静仪); LI Weiming (李伟明); HAO Li (郝丽); LI Xiaochan (李晓婵); LUO Juanjuan (罗娟娟); CAI Hongtao (蔡红涛) (Journal of International Translational Medicine Limited, 2021)
Objective To investigate the status and influencing factors of clinical communication competency among male psychiatric nurses in Guangdong. Methods A cross-sectional survey of 191 male psychiatric nurses was conducted using the Nurses' clinical Communication Competency Scale. Results The average score of clinic communication competency was (3. 79±0. 80). From high to low, the scores of each dimension were: team communication ability was (3. 91±0. 85); emotional perception ability was (3. 82±0. 83); basic verbal communication ability was (3. 81±0. 81); basic non-verbal communication ability was (3. 79±0. 82); emotional support ability was (3. 77±0. 83); communication ability in difficult situations was (3. 75±0. 81). Male nurses' position was the main factor affecting the score of clinical communication competency and the difference was statistically significant (P<0. 05). Conclusion The clinical communication competency of male psychiatric nurses in Guangdong Province was at a medium level, and the scores of emotional support ability and communication ability in difficult situations were relatively low. Therefore, the psychiatric nursing managers should take systematic and targeted training to further improve the clinical communication competency of male psychiatric nurses. (目的 调查广东省精神科男护士临床沟通能力水平, 分析影响因素。方法 采用护士临床能力沟通量表, 通过电子问卷形式对191名精神科男护士进行横断面调查。结果 广东省精神科男护士沟通能力均分总分为(3. 79±0. 80)分。各维度得分从高到低依次为: 团队沟通能力(3. 91±0. 85)分, 情感感知能力(3. 82±0. 83)分, 基本语言沟通能力( 3. 81±0. 81 )分, 基本非语言沟通能力(3. 79±0. 82)分, 情感支持能力(3. 77±0. 83)分, 困难情景沟通能力(3. 75±0. 81)分。职务是影响临床沟通能力得分的主要因素, 差异有统计学意义(P<0. 05)。结论 广东省精神科男护士的临床沟通能力呈中等水平, 情感支持能力与困难情景沟通能力得分相对偏低, 精神科护理管理者应采取系统的针对性培训, 以进一步提高精神科男护士的临床沟通能力。)